Preliminary Gene Characterization of α-Amylase from Bacillus amyloliquefaciens UMAS 1002 - Muhammad Suhaib, M. H.; Mohd Hasnain, Hussain; Awang Ahmad Sallehin, Awang Husaini; Kopli, Bujang; Dayang Salwani, Awang Adeni; Mohd Azib, Salleh (Universiti Malaysia Sarawak (UNIMAS), 2013)
Characterization of α-amylase gene sequence produced by Bacillus amyloliquefaciens UMAS 1002, a cellulolytic and amylolytic bacilli isolated from sago pith waste is described here. The amyE gene encoding the α-amylase was isolated by polymerase chain reaction. The 1,980 bp of amyE gene corresponding to 660 amino acids showed 99% homology to the α-amylase sequence from Bacillus subtilis X-23 (GenBank: BAA31528). The α-amylase sequence of B. amyloliquefaciens UMAS 1002 (GenBank: KC800929) differs from that of B. subtilis X-23 by 5 amino acids. In silico analysis of α-amylase from B. amyloliquefaciens UMAS 1002 showed similar characteristics compared to α-amylase from B. subtilis X-23